Digital Transformation Maturity Measurement (DTMM) for the Oil and Gas Industry - Chatchai Kongdachudomkul; Wilert Puriwat; Danupol Hoonsopon (HighTech and Innovation Journal, 2025)
This study develops and validates a Digital Transformation Maturity Measurement (DTMM) framework tailored to the oil and gas industry, addressing sector-specific regulatory and technological challenges. A mixed-methods approach was employed, integrating semi structured interviews with 10 senior executives and a survey of 240 industry professionals. The data were analyzed via structural equation modeling (SEM) and confirmatory factor analysis (CFA) to assess five maturity factors—leaders, staff, organization, technology, and value for stakeholders—across three key success indicators: financial performance, customer/internal user value, and environmental and societal value. The findings highlight Technology and Value for Stakeholders as the most influential transformation drivers, significantly improving operational efficiency and sustainability. Unlike prior models, the proposed DTMM integrates financial, technological, and sustainability dimensions into a unified assessment tool. This study contributes to the digital transformation literature by offering an empirically validated framework for evaluating and guiding strategic digital initiatives. Policymakers and industry leaders can leverage these insights to enhance digital maturity, prioritize high-impact strategies, and drive sustainable growth in an increasingly competitive landscape.